A uses and gratifications perspective on media use by refugees from Myanmar and Pakistan in Malaysia - Mokhtar, Aida; Mohd Rashid, Nurul Miza (ISTAC, International Islamic University Malaysia, 2017)
A refugee is defined by the 1951 Convention Relating to the Status of Refugees, Article 1(A) (2) as a person who encounters the fear of being persecuted for their race, religion, nationality, membership of a particular social group or political opinion, resides away from his or her own country and is not willing to be protected by the country. The United Nations Refugee Agency Malaysia (UNHCR) registered 149,100 refugees and asylum-seekers as of the end of August 2017. Most of these were from Myanmar, comprising Rohingya (n=61,000) and Chin (n=9,900) people, followed by Pakistanis (n=4,200). Given their circumstances and the apparent dearth of literature in the area, there is an urgent need to explore the utilisation of media and non-media activities by refugees from Myanmar and Pakistan in terms of use and gratifications of such activities, as undertaken in this research, based on Uses and Gratifications (U&G) theory, which comprises five elements: the audience is active, the link between need gratification and media choice lies with audience members, there are media and other needs competing (non-media needs), many goals of mass media use can be generated from data supplied by audience members, and audience orientations should be examined on their own terms (without considering culture). The study develops U&G theory, contributes to current studies, and provides an insight on refugee needs gratified by media and non-media activities, particularly in terms of communities in Malaysia. The study embraced a multiple case-study research design by investigating the two refugee communities in depth, through interviews.